Achieving non-malicious arbitrary fault tolerance in Paxos through hardening techniques - Barbieri, Rodrigo Rocco (Universidade Federal de São Carlos, 2016)
Due to the widespread adoption of distributed systems when building applications, demand for reliability and availability has increased. These properties can be achieved through replication techniques using algorithms that must be capable of tolerating faults. Certain faults such as arbitrary faults, however, may be more difficult to tolerate, resulting in more complex and resource intensive algorithms that end up being not very practical to use. Using an existing benign fault-tolerant middleware based on Paxos, we propose and experiment with the usage of consistency validation techniques and a distributed validation mechanism to harden it, thus allowing any application built on top of this hardened middleware to tolerate non-malicious arbitrary faults.
Keywords: Sistemas operacionais distribuídos (Computadores); Distributed operating systems (Computers); Algorítmos computacionais; Computer algorithms; Fault tolerance; Paxos; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO